2009
DOI: 10.1590/s0103-05822009000100005
|View full text |Cite
|
Sign up to set email alerts
|

Soropositividade para doença celíaca em crianças e adolescentes com baixa estatura

Abstract: OBJETIVO: Avaliar a frequência da positividade do marcador sorológico para doença celíaca em crianças e adolescentes com baixa estatura, utilizando-se o anticorpo anti-transglutaminase humana como teste de triagem. MÉTODOS: Estudo descritivo com amostra obtida por conveniência. Foi realizado no período de abril a setembro de 2004 no Ambulatório Geral de Pediatria do Instituto Materno Infantil Professor Fernando Figueira e no Ambulatório de Crescimento e Desenvolvimento do Hospital das Clínicas. Foram considera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Data of studies performed in specific populations identified that the positivity prevalence of the anti-TtG antibody varied from 0.28 to 1.76% in adolescents and adults from the South, Southeast and Northeast areas 12,17,[19][20][21] . Seroprevalence through the anti-tTG IgA antibody of 3.80 22 , 3.37 4 and 4.56% 14 were seen in children and adolescents of Pernambuco, percentages that are expressively higher than that seen (0.49%) in adolescents from Salvador. It is worth mentioning that studies done in Pernambuco were carried out in hospital and ambulatory populations, also one of them was performed with children and adolescents with low stature, which can be an atypical form of CD presentation 22 .…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Data of studies performed in specific populations identified that the positivity prevalence of the anti-TtG antibody varied from 0.28 to 1.76% in adolescents and adults from the South, Southeast and Northeast areas 12,17,[19][20][21] . Seroprevalence through the anti-tTG IgA antibody of 3.80 22 , 3.37 4 and 4.56% 14 were seen in children and adolescents of Pernambuco, percentages that are expressively higher than that seen (0.49%) in adolescents from Salvador. It is worth mentioning that studies done in Pernambuco were carried out in hospital and ambulatory populations, also one of them was performed with children and adolescents with low stature, which can be an atypical form of CD presentation 22 .…”
Section: Discussionmentioning
confidence: 72%
“…Seroprevalence through the anti-tTG IgA antibody of 3.80 22 , 3.37 4 and 4.56% 14 were seen in children and adolescents of Pernambuco, percentages that are expressively higher than that seen (0.49%) in adolescents from Salvador. It is worth mentioning that studies done in Pernambuco were carried out in hospital and ambulatory populations, also one of them was performed with children and adolescents with low stature, which can be an atypical form of CD presentation 22 .…”
Section: Discussionmentioning
confidence: 72%